“It’s scary here.” Haunted landscape as a research tool to look into post-expulsion landscapes - Ćwiek-Rogalska, Karolina (Polskie Studia Krajobrazowe, 2020)
The article deals with the idea of “haunted landscape” as a research tool in analyzing post-expulsion landscapes. I propose a new perspective on analyzing narrations concerning expulsion and resettlements of lands where a drastic demographic change took place. I use existing research connected with the idea of Jacques Derrida’s hauntology, as well as other analytical sources dealing with folktales of different regions. As material for analysis, I propose various records from ethnographic research conducted in the Czechoslovak borderlands, stored at the Institute of Ethnology of the Czech Academy of Sciences, concerning the space of a “traditional house” and the new settlers’ views on their new home.